Zachodnioeuropejskie impresje w cyklu szkiców Aleksandra Kuprina "Lazurowe wybrzeża" = Western European impressions in a series of Aleksander Kuprin's sketches "Azure Coast" - Bielniak, Nel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 1912 Aleksander Kuprin travelled abroad in order to improve his health condition. The travels resulted in creating both epistolary materials and a series of sketches, "Azure Coast" (1913), which are characteristic because of their ambivalence.
Keywords: Kuprin, Aleksander Iwanowicz (pisarz rosyjski; 1870-1938); literatura rosyjska; literatura europejska - motywy; 20 w.